Engaging Patients with Headache in the Veterans Health Administration (VHA): ACTIvated Veterans Engagement Group (ACTIVE) to Improve Delivery of Patient-Centered Headache Services - Olivia M. Datre BA; Sean A. Baird MA; Hayley M. Lindsey BA; Roberta E. Goldman PhD; Jason J. Sico MD; Teresa M. Damush PhD (Journal of Patient Experience)
In 2018, the Veterans Health Administration (VHA) established the original 19 Headache Centers of Excellence (HCoE) program, and an evaluation center. This study utilized a Veteran engagement group method to elicit input from Veteran patients living with chronic headache on daily needs, social determinants of health, and preferences and suggestions for headache programs, services, and research priorities. Four engagement groups were conducted between July 13 th and August 22 nd of 2022 with Veterans who experience headache and received care at a VHA HCoE. Engagement groups were audio-recorded, de-identified, transcribed, and analyzed using rapid qualitative content matrix analysis. Participants also completed a baseline survey on demographics, technology use, headache history, and health. Patients perceived care coordination, social support, gender specific preferences and access to complementary and integrative therapies to be important aspects of headache care delivered by HCoEs. Participants expressed strong interest in effective, interactive peer support groups to share and learn from each other's experiences with headaches and treatments. Findings underscore the demand for coordinated, interdisciplinary headache care integrating complementary health approaches and addressing gender-specific needs.